A proposition for a clasification model of electrodes for resistance spot welding - Brestovački, Lazar; Bela, Sabo; Dakić, Jovica (Journal of Production Engineering, 1993)
A classification model of electrodes for resistance spot welding takes into account all the information about electrodes required for a complete definition: the material, the method of production, the shape of the electrode part for positioning and clamping, the forms of the electrode tip, the contours of the electrode, the cooling system of the electrode tip, the cross-sectional shape of the electrode, the maximum dimensions of electrode face shapes, and the dimensions of the cross section of the electrode. This paper is based on existing national standards, German (DIN) and Yugoslav (JUS), recommendations from other technical literature, and practical experience. A proposed model of classification could be applied during the design phase as well as during the execution of resistance spot welding.